Justification of the choice intraligamentary anesthesia in outpatient dental practice (Эндодонтия Today, 2020)
The efficacy and safety of use intraligamentary anesthesia in the treatment of caries and its complications single-rooted and multi-rooted teeth using 4% articaine with epinephrine 1:100 000, 1:200 000 and without a vasoconstrictor. Effectiveness of anesthesia was assessed using objective methods elektroodontometrii and registration of microcirculation dental pulp. Security is controlled by monitoring indices of Central hemodynamics.